Analisis Gaya Bahasa dan Majas Pada Lagu “Raksa” Karya Soegi Bornean - Reinaldo, Christopher; Muhammad Taufik (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article explores the richness of language styles and speech used in the lyrics of the song